Field reports form for submitting seasonal observations of Iowa birds, Matthew Kenne, spring 1992 - Kenne, Matthewet al (1992)
List of birds and locations contributed by Matthew Kenne with observers Bobbi Webber and Dave Bunkofske. The field notes include detailed descriptions of several birds. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed